VaSDC1 Is Involved in Modulation of Flavonoid Metabolic Pathways in Black and Red Seed Coats in Adzuki Bean (Vigna angularis L.) - Chu, Liwei; Zhao, Pu; Wang, Kaili; Zhao, Bo; Li, Yisong; Yang, Kai; Wan, Ping (Frontiers in Plant Science, 2021)
Seed coat colour is an important nutritional quality trait. Variation of anthocyanins and flavonoids induce the diversity of seed coat colour in adzuki bean. Red seed coat and black seed coat are important adzuki bean cultivars. Insights into the differences of flavonoid metabolic pathways between black and red adzuki bean is significant. In this study, we explored that the seed coat colour difference between the red (Jingnong6) and the black (AG118) is caused by the accumulation of anthocyanins. The RNA-Seq and qRT-PCR result showed that VaSDC1 gene, an R2R3-MYB transcription factor should be the key gene to regulate the black and red seed coat colour. In three different colouring stages of seed development, VaSDC1 was specifically expressed in the black seed coat (AG118) landrace, which activates the structural genes of flavonoid metabolic pathways. As a result, this caused substantial accumulation of anthocyanins, and created a dark blue-black colour. In the red (Jingnong6) seed coat variety, low expression levels of VaSDC1 resulted in lower accumulation of anthocyanins than in AG118. In addition, VaSDC1 was genetically mapped in the interval between SSR markers Sca326-12, Sca326-4, and BAgs007 on chromosome 3 using an F4 segregating population derived from the cross between Jingnong6 and AG118. These results will facilitate the improvement of nutritional quality breeding in adzuki bean.